Discovery of a sexual cycle in Aspergillus clavatus - Swilaiman, Sameira S.; Ashour, Adel O.; Dyer, Paul S. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Aspergillus clavatus is an opportunistic human pathogen causing invasive aspergillosis. It is an economically important species because it can grow on rotting fruit (apples) and stored food products and able to produce a variety of mycotoxins. It has only been known to reproduce mitotically. This study aimed to discover the sexual reproduction in A. clavatus. Methods: Identifying mating-type (MAT1-1 or MAT1-2) using PCR of 20 worldwide clinical and environmental isolates, crossing isolates on oatmeal agar in darkness with plate sealing, Recombination in ascospore offspring was demonstrated using molecular markers. Results: There were similar ratios of the two mating types (45% MAT1-1 n = 9, 55% MAT1-2 n = 11). A. clavatus possesses a functional sexual cycle with mature cleistothecia fawn to brown/yellow in color, containing heat-resistant ascospores, produced after four weeks incubation at 25˚C and 28˚C on Nescofilm- sealed oatmeal agar plates. The cleistothecia contain hyaline ascospores that have two equatorial ridges. Recombination, leading to increased genotypic variation demonstrated in the ascospore offspring using molecular markers. Conclusion: The ability of A. clavatus to undergo sexual reproduction is highly significant in understanding the biology and evolution of the species. The presence of a sexual cycle provides an invaluable tool for classical genetic analysis and will facilitate research into the genetic basis of pathogenicity and fungicide resistance.